Film Music : A Very Short Introduction - Kalinak, Kathryn Marie (New York Oxford University Press, 2010)
Film music is as old as cinema itself. Years before synchronized sound became the norm, projected moving images were shown to musical accompaniment, whether performed by a lone piano player or a hundred-piece orchestra. Today film music has become its own industry, indispensable to the marketability of movies around the world. Film Music: A Very Short Introduction is a compact, lucid, and thoroughly engaging overview written by one of the leading authorities on the subject. After opening with a fascinating analysis of the music from a key sequence in Quentin Tarantino's Reservoir Dogs, Kathryn.
Include Illustrations and Index
Keywords: Motion picture music -- History and criticism -- Theory. Motion picture music. -- MUSIC -- Instruction & Study